A climatologic investigation of the SARS-CoV outbreak in Beijing, China - Yuan, Jingsong (Am J Infect Control, 2006)
The first cases of severe acute respiratory syndrome (SARS) were identified in November 2002, in Guangdong Province, China. The epidemic spread rapidly within China and internationally, with 8454 recorded infections and 792 deaths by June 15, 2003. Temperature, relative humidity, and wind velocity were the three key meteorological determinants affecting the transmission of SARS. The peak spread of SARS occurred at a mean temperature of 16.9°C (95% CI, 10.7°C to 23.1°C), with a mean relative humidity of 52.2% (95% CI, 33.0% to 71.4%) and wind speed of 2.8 ms(−1) (95% CI, 2.0 to 3.6 ms(−1)). In northern China, these conditions are most likely to occur in the spring and suggest that SARS has a seasonal nature akin to viruses such as influenza and the common cold. A regression equation [Formula: see text] was derived to represent the optimal climatic conditions for the 2003 SARS epidemic. Further investigations in other regions are necessary to verify these results.